2023
DOI: 10.1186/s40634-023-00589-w
|View full text |Cite
|
Sign up to set email alerts
|

The role of bone marrow stimulation in rotator cuff repair: a systematic review and meta‐analysis

Abstract: Purpose The objective of this study was to investigate whether RCR (rotator cuff repair) with BMS (bone marrow stimulation) can provide a lower retear rate and better shoulder function than arthroscopic RCR alone in rotator cuff tear (RCT) patients. Method The PubMed, Cochrane Library, EMBASE and Web of Science databases were searched until Feb 2022. Risk of bias for randomized controlled trials was evaluated by two independent reviewers with Cochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous systematic reviews 1,18,31,32 have found that although the clinical outcomes were similar, arthroscopic rotator cuff repair with BMS had a significantly higher healing rate than conventional rotator cuff repair. However, these systematic reviews included retrospective cohort studies, which have a low level of evidence and can have some biases and limitations.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Previous systematic reviews 1,18,31,32 have found that although the clinical outcomes were similar, arthroscopic rotator cuff repair with BMS had a significantly higher healing rate than conventional rotator cuff repair. However, these systematic reviews included retrospective cohort studies, which have a low level of evidence and can have some biases and limitations.…”
Section: Discussionmentioning
confidence: 89%
“…Li and Zhang 18 included 4 randomized controlled trials and 4 retrospective cohort studies in their review. Yang et al 31 conducted a review that involved 5 randomized controlled trials and 4 cohort studies. Zhang et al 32 included 4 randomized controlled trials and 4 retrospective cohort studies in their review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation